Contemporary Tibetan Monastic Business and the Corporate Form - Caple, Jane (Implicit Religion, 2024)
In early twenty-first century Tibet, many Geluk monasteries established capital funds that they invested in small businesses—the Geluk being one of the main Tibetan Buddhist traditions. Drawing on fieldwork in northeast Tibet, this article examines debates surrounding this monastic engagement in business, asking why it proved contentious despite historical and canonical precedent. I approach this question by thinking about monastic business engagement in relation to Geluk monasticism as a distinctive corporate form. Foregrounding how monks made sense of what they were doing as corporate actors, I examine common rationales, concerns, and questions of legitimacy at the heart of arguments both for and against monastic business development, and how these related to the monastic corporation’s core concern with preservation and continuity. The article concludes with some broader reflections on what these debates can tell us about the ongoing process of corporation-making, suggesting some possible avenues for future research.